Pengaruh Gender, Usia, IPK Terhadap Literasi Keuangan Mahasiswa Jurusan Akuntansi Politeknik Negeri Malang - Syuliswati, Atika (STIE Malangkucecwara, 2019)
The purpose of this study was to examine the direct effect of variables gender, age, GPA to financial literacy. This research is a quantitative research and the sample consist of 142 students Accounting Department of State Polytechnic Malang. Data analysis method used in this research is multiple linear regression analysis with the help of SPSS Version 21 program. The results showed gender, age, and GPA significant and positive effect on financial literacy.